EMMPRIN regulates β1 integrin‐mediated adhesion through Kindlin‐3 in human melanoma cells. Issue 6 (16th April 2015) - Delyon, Julie; Khayati, Farah; Djaafri, Ibtissem; Podgorniak, Marie‐Pierre; Sadoux, Aurélie; Setterblad, Niclas; Boutalbi, Zineb; Maouche, Kamel; Maskos, Uwe; Menashi, Suzanne; Lebbé, Céleste; Mourah, Samia
Abstract EMMPRIN is known to promote tumor invasion through extracellular matrix (ECM) degradation. Here we report that EMMPRIN can regulate melanoma cell adhesion to the ECM through an interaction with β1 integrin involving kindlin‐3. In this study, EMMPRIN knockdown in the human melanoma cell line M10 using siRNA decreased cell invasion and significantly increased cell adhesion and spreading. A morphological change from a round to a spread shape was observed associated with enhanced phalloidin‐labelled actin staining. In situ proximity ligation assay and co‐immunoprecipitation revealed that EMMPRIN silencing increased the interaction of β1 integrin with kindlin‐3, a focal adhesion protein. This was associated with an increase in β1 integrin activation and a decrease in the phosphorylation of the downstream integrin kinase FAK. Moreover, the expression at both the transcript and protein level of kindlin‐3 and of β1 integrin was inversely regulated by EMMPRIN. EMMPRIN did not regulate either talin expression or its interaction with β1 integrin. These results are consistent with our in vivo demonstration that EMMPRIN inhibition increased β1 integrin activation and its interaction with kindlin‐3. To conclude, these findings reveal a new role of EMMPRIN in tumor cell migration through ß1 integrin/kindlin‐3‐mediated adhesion pathway.